Two years of polar winter observations with the ASTEP400 telescope - Abe, L; Rivet, J; Agabi, A; Aristidi, E; Mekarnia, D; Goncalves, I; Guillot, T; Barbieri, M; Crouzet, N; Fressin, F; Schmider, F; Fantei-Caujolle, Y; et al. (2012)
The ASTEP program is dedicated to exo-planet transit search from the Concordia Station located at Dome C, Antarctica. It comprises two instruments: a fixed 10cm refractor pointed toward the celestial South Pole, and a 400mm Newton telescope with a 1×1 degree field of view. This work focuses on the latter instrument. It has been installed in November 2009, and has been observing since then during the two polar winters 2010 and 2011. After presenting the main science observing programs, we review the telescope installation, performance, and describe its operating conditions as well as the data reduction and handling strategy. The resulting lightcurves are generally very stable and of excellent quality, as shown by continuous observations of WASP-19 that we present here. © 2012 SPIE.